2018
DOI: 10.1084/jem.20171265
|View full text |Cite
|
Sign up to set email alerts
|

ApoE facilitates the microglial response to amyloid plaque pathology

Abstract: Increasing evidence suggests that apoE influences the innate immune response in neurodegeneration. Here, Ulrich et al. report that apoE influences amyloid plaque morphology and the microglial response to amyloid plaques, along with plaque-associated neuronal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
185
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(206 citation statements)
references
References 57 publications
18
185
3
Order By: Relevance
“…Previous studies from our lab and others showed that complete ablation [59][60][61][62][63] or reduction [8][9][10] of apoE levels results in a decrease of Aβ pathology, particularly a marked reduction of fibrillar Aβ in the brain. However, it was difficult to assess the contribution of peripheral apoE ablation to phenotypes found in the brain in complete Fig.…”
Section: Plasma Lipid Alterations In Mice Lacking Liver-derived Apoementioning
confidence: 66%
“…Previous studies from our lab and others showed that complete ablation [59][60][61][62][63] or reduction [8][9][10] of apoE levels results in a decrease of Aβ pathology, particularly a marked reduction of fibrillar Aβ in the brain. However, it was difficult to assess the contribution of peripheral apoE ablation to phenotypes found in the brain in complete Fig.…”
Section: Plasma Lipid Alterations In Mice Lacking Liver-derived Apoementioning
confidence: 66%
“…Apoe −/− mice were significantly associated with ivory module (N = 64, p = 9.7 × 10 −6 ), while the skyblue3 (N = 80, p = 4.6 × 10 −13 ) (Figure 3; Figure 4; Supplemental Table 3) module were significantly associated with both Apoe −/− and APOEε4 strains. Pathway analysis identified that the ivory mouse module was enriched in inflammation and microglia related pathways such as osteoclast differentiation, staphylococcus aures infection, phagosome, and endocytosis (Figure 2B), implicating an important role of Apoe in inflammatory and microglia related functions [4042]. Brown (N = 1778, p = 3.1 × 10 −7 ), lightcyan1 (N = 1206, p = 1.9 × 10 −5 ), black (N = 685, p = 2.0 × 10 −2 ), plum1 (N = 80, p = 1.0 × 10 −2 ), and brown4 (N = 55, p = 0.04) modules were significantly associated with Clu −/− (Figure 3; Figure 4; Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a potential cycle involves initial microglial reaction, which results in upregulation and secretion of ApoE, leading to altered amyloid deposition with ApoE incorporated into the plaque, which binds to TREM2 and continues the cycle. This potential cycle is supported by work demonstrating that APP/PS1 mice crossed to Apoe-KO mice have significant reductions in the number of plaque-associated microglia (Ulrich et al, 2018). Furthermore, treatment of an AD mouse model with antibody specifically against non-lipidated ApoE (including that found in plaques) reduced amyloid deposition (Liao et al, 2018).…”
Section: Trem2 Signaling Networkmentioning
confidence: 94%